Mitochondrial cytochrome c(1) is a collapsed di-heme cytochrome - Baymann, Frauke (National Academy of Sciences, 2004)
Cytochrome c(1) from mitochondrial complex III and the di-heme cytochromes c in the corresponding enzyme from ε-proteobacteria have so far been considered to represent unrelated cytochromes. A missing link protein discovered in the genome of the hyperthermophilic bacterium Aquifex aeolicus, however, provides evidence for a close evolutionary relationship between these two cytochromes. The mono-heme cytochrome c(1) from A. aeolicus contains stretches of strong sequence homology toward the ε-proteobacterial di-heme cytochromes. These di-heme cytochromes are shown to belong to the cytochrome c(4) family. Mapping cytochrome c(1) onto the di-heme sequences and structures demonstrates that cytochrome c(1) results from a mutation-induced collapse of the di-heme cytochrome structure and provides an explanation for its uncommon structural features. The appearance of cytochrome c(1) thus represents an extension of the biological protein repertoire quite different from the widespread innovation by gene duplication and subsequent diversification.